Armstrong : the adventurous journey of a mouse to the moon - Kuhlmann, Torben, 1982-; Kuhlmann, Torben, 1982- (North South, 2019)
A long time ago a mouse learned to fly ... and crossed the Atlantic. But what happened next? Torben Kuhlmann's book transports readers to the moon and beyond! On the heels of Lindbergh: The Tale of a Flying Mouse comes Armstrong: A Mouse on the Moon--where dreams are determined only by the size of your imagination and the biggest innovators are the smallest of all. The book ends with a brief non-fiction history of human space travel--from Galileo's observations concerning the nature of the universe to man's first steps on the moon.